Bone densitometry versus bone histomorphometry in renal transplanted patients: a cross‐sectional study. (19th May 2021) - Ferreira, Ana Carina; Mendes, Marco; Silva, Cecília; Cotovio, Patrícia; Aires, Inês; Navarro, David; Caeiro, Fernando; Salvador, Rute; Correia, Bruna; Cabral, Guadalupe; Nolasco, Fernando; Ferreira, Aníbal
Summary: Bone loss leads to increase risk of fractures in renal transplantation. The aim of this study was to analyse the relationship between bone densitometry (DXA) findings, bone histomorphometry and bone‐related molecules 1‐year after renal transplantation. We performed a cross‐sectional study of de novo renal transplanted patients that agreed to perform a bone biopsy and a DXA examination 1 year after transplantation. All patients underwent a laboratory evaluation, bone biopsy, DXA examination and cardiac CT 1 year after transplantation. 67 patients were included, 16 had a normal examination, and 18 patients were classified as having osteoporosis by DXA. Correlations between bone mineral density and T ‐scores of total femur and femoral neck were the ones that best correlated with bone volume assessed by a bone biopsy. The sensitivity of DXA for osteoporosis diagnosis was 47.0%, and the specificity was 81.2%. The positive predictive value was 50.0%, and the negative predictive value (NPV) was 80.0%. DXA parameters also correlated with klotho and sclerostin serum levels. In this population, a normal examination excluded the presence of osteoporosis, helping in identifying patients that would not benefit from therapy. Overall, densitometry in total femur and femoral neck correlated well with bone volume measured by bone biopsy.